UJI ANALISIS KUALITATIF DAN KUANTITATIF KADAR VITAMIN C PADA SEDIAAN KOSMETIK LOTION YANG BEREDAR DI KAB. MAROS DENGAN METODE SPEKTROFOTOMETER Uv-Vis - Hashary, A Rufaidah; Arifuddin Yunus; Wati (Jurnal Riset Kefarmasian Indonesia, 2025)
Cosmetics are an inseparable part of women's lives in particular and are used every day. Lotions are widely used to moisturize the skin and to brighten the skin. Lotion can be used for all skin types for teenagers aged 15 years and over. Vitamin C has various benefits, including as an antioxidant against pollution, sun exposure, brightening the skin, delaying the effects of aging, and increasing collagen formation which makes the skin supple, smooth and bright. The aim of the research was to determine the vitamin C content in cosmetic lotions according to the standards/labels circulating in the Maros district. The research was carried out using qualitative analysis methods in the pharmaceutical chemistry analysis laboratory of STIKes Salewangang Maros where the samples were lotion cosmetic products containing vitamin C at kab. Maros as stated on the product packaging/label and analyzed using a Uv-Vis spectrophotometer. The results of the research obtained showed that all lotion cosmetic preparations contained vitamin C with different percentage levels for each concentration, where lotion samples that did not have a distribution permit obtained high levels of Vitamin C, while lotions that had a distribution permit showed high levels of Vitamin C. not excessive, so it is safe to use for a long time.